Can AI Support Ethical Resource Allocation in Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Resource allocation in healthcare has always been a complex and challenging issue. With limited resources and ever-increasing demand, healthcare systems worl...
Keywords: AI Ethics in Healthcare; Support; Ethical; Resource; Artificial Intelligence; Healthcare; Digital Health